Impact of Draw Solution Concentration on Forward Osmosis Process: A Simulation Study - Alfahel, Radwan; Hafiz, MhdAmmar; Hawari, Alaa H. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
In this study, a simulation model was used to evaluate the performance of forward osmosis process. A solution of low salinity was used as the feed solution in forward osmosis to dilute saline solution (i.e. draw solution) for further desalination. The paper evaluated the effect of the draw solution concentration on the recovery rate and energy consumption in forward osmosis. It was found that increasing the concentration of draw solution increased the recovery rate. Also, while increasing concentration of draw solution, energy consumption decreased. The maximum recovery rate of 33% was achieved using (0.5M NaCl) draw solution and a flow rate of 40000 m3/day. The specific power consumption was 0.21 kWh/m3.